Taking Our Own Medicine: Revising a Graduate Level Methods Course on Curriculum Change - Kraus, Rudolf; Shapiro, Lesley J. (Innovations in Science Teacher Education, 2018)
Implementing the Next Generation Science Standards presents challenges for practicing teachers. This article presents our reflection on creating and revising a class designed to teach inservice teachers about curriculum change and the Next Generation Science Standards. In its initial iteration, the course was designed to address the intellectual and practical aspects of this change in standards. Interaction with teachers, as well as gathered course reflections, indicated that addressing the process of curriculum change is both a practical task and an emotional one.